DETECTION OF ESBL AND MBL AMONG GRAM NEGATIVE ENTEROBACTERIACEAE ISOLATES FROM DIABETIC FOOT ULCER IN CHENNAI - ARUMUGAM SURESH,; GOPAL MUTHU,; SEETHARAMAN SRIVANI, (International Journal of Pharma and Bio Sciences, 2014)
Diabetic foot infection (DFI) is poly-microbial in nature, pathogenic microorganism such as Pseudomonas spp., Enterococcus spp. and Proteus spp. are mainly responsible for continuing and extensive tissue destruction with the poor blood circulation of the foot. The present study was aimed to characterize the ESBL and MBL producing non-fermentative and gram negative bacterial isolates from diabetic foot ulcer (DFU) by phenotypic and genotypic methods. Total of 171 pathogenic microorganisms was isolated from 123 DFU pus sample, 41 isolates were found to be non-fermentative and non enterobacteriaceae isolates among these 33 isolates were Pseudomonas aeruginosa and 8 isolates were Acinetobacter baumannii. ESBL and MBL positivity were found to be 48% (20/41) and 70.7% (29/41) respectively. ESBL gene amplification was done by universal primers such as blaCTX-M, blaTEM and blaSHV. Genotypic ESBL positivity was found to be 2.4%, 31.7%, and 8%forrespective genes such as blaCTX-M, blaTEM, and blaSHV genes. A detailed knowledge of the susceptibility to antimicrobial agents is necessary to facilitate the development of effective strategies to combat the growing problem of resistance especially the ESBL positive strains. There is high percentage of antibiotic resistance found in our isolates; which warrants the use of antibiotic policy as well as proper surveillance programs.